Diet or medication in primary care patients with IBS: the DOMINO study - a randomised trial supported by the Belgian Health Care Knowledge Centre (KCE Trials Programme) and the Rome Foundation Research Institute. Issue 11 (28th April 2022) - Carbone, Florencia; Van den Houte, Karen; Besard, Linde; Tack, Céline; Arts, Joris; Caenepeel, Philip; Piessevaux, Hubert; Vandenberghe, Alain; Matthys, Christophe; Biesiekierski, Jessica; Capiau, Luc; Ceulemans, Steven; et al.
Abstract : Background: In Europe, IBS is commonly treated with musculotropic spasmolytics (eg, otilonium bromide, OB). In tertiary care, a low fermentable oligosaccharides, disaccharides, monosaccharides and polyols (FODMAP) diet provides significant improvement. Yet, dietary treatment remains to be explored in primary care. We evaluated the effect of a smartphone FODMAP-lowering diet application versus OB on symptoms in primary care IBS. Methods: IBS patients, recruited by primary care physicians, were randomised to 8 weeks of OB (40 mg three times a day) or diet and followed for 24 weeks. We compared IBS Symptom Severity Score and the proportion of responders (improvement ≥50 points) in all patients and the subgroup fulfilling Rome IV criteria (Rome+). We also evaluated treatment efficacy, quality of life, anxiety, depression, somatic symptom severity (Patient Health Questionnaire (PHQ15, PHQ9)) and treatment adherence and analysed predictors of response. Results: 459 primary care IBS patients (41±15 years, 76% female, 70% Rome+) were randomised. The responder rate after 8 weeks was significantly higher with diet compared with OB (71% (155/218) vs 61% (133/217), p=0.03) and more pronounced in Rome+ (77% (118/153) vs 62% (98/158), p=0.004). Patients allocated to diet (199/212) were 94% adherent compared with 73% with OB (148/202) (p<0.001). The significantly higher response rate with diet was already observed after 4 weeks (62% (132/213) vs 51% (110/215), p=0.02) and a high symptom response persisted during follow-up. Predictors of response were female gender (OR=2.08, p=0.04) for diet and PHQ15 (OR=1.10, p=0.02) for OB. Conclusion: In primary care IBS patients, a FODMAP-lowering diet application was superior to a spasmolytic agent in improving IBS symptoms. A FODMAP-lowering diet should be considered the first-line treatment for IBS in primary care. Trial registration number: NCT04270487 .